1642d Capacity building in osh: a view from the developing country. (24th April 2018) - Pingle, S; Parekh, R; Mavalankar, D
Abstract : Access to specialised occupational health services is low across the world. However, the problem is very acute in developing countries due to various factors. Equitable health system cannot be achieved unless the lack of basic occupational health facilities for all the working population are addressed. India is an important and major developing country and represents the challenges in the developing countries to a great extent. The most important OSH needs in developing countries such as India are: legislation to extend OSH coverage to all sectors of working life including the unorganised sector, spreading the awareness about OSH, development of OSH infrastructure and OSH professionals. Integration of occupational health with primary health care. To address the increasing need of occupational health experts, capacity building is needed on a massive scale. The status of occupational health capacity in India reviewed from the available data and literature indicates huge gaps in the requirement and available capacity. The capacity established by the government has been grossly inadequate. Further, currently the services are aimed at organised sector and the huge need in unorganised sector is not being addressed. Various nongovernmental international and national organisations have stepped in and have initiated various sensitisation, awareness and training programs with support from donors. Some of these programs have supported training of few experts from developing countries including India. A case study of occupational health training and sensitisation of health care providers at primary level will be discussed. It is an initiative by Indian Association of Occupational Health which is a nongovernmental voluntary professional organisation of OH experts. Two of the international programs will also be discussed. This presentation will review some of these initiatives and their outcome, the challenges faced and way forward. It will also discuss the potential role of expert associations.